Oxidative and Inflammatory Imbalance in Placenta and Kidney of sFlt1-Induced Early-Onset Preeclampsia Rat Model - Santana-Garrido, Álvaro (2022)
Preeclampsia (PE) is a pregnancy-specific disorder characterized by the new onset of hypertension plus proteinuria and/or end-organ dysfunction. Here, we investigate the role of the nicotinamide adenine dinucleotide phosphate (NADPH) oxidase system as a major component of reactive oxygen species generation, in a rodent model of early-onset preeclampsia induced by excess sFlt1 (soluble fms-like tyrosine kinase 1). Placenta and kidney samples were obtained from normal pregnant and PE rats to measure the sFlt1/PlGF (placental growth factor) ratio in addition to oxidative stress-related parameters, including the activities and expressions of NADPH oxidase isoforms (NOX1, NOX2, and NOX4), components of nitric oxide (NO) metabolism, and antioxidant enzymes. Peroxisome proliferator-activated receptors (PPARα, PPARγ) and cytokines IL1β, IL3, IL6, IL10, and IL18 were also measured to evaluate the inflammation status in our experimental setting. Excessive O2●− production was found in rats that were treated with sFlt1; interestingly, this alteration appears to be mediated mainly by NOX2 in the placenta and by NOX4 in the kidney. Altered NO metabolism and antioxidant defense systems, together with mitochondrial dysfunction, were observed in this model of PE. Preeclamptic animals also exhibited overexpression of proinflammatory biomarkers as well as increased collagen deposition. Our results highlight the role of NADPH oxidase in mediating oxidative stress and possibly inflammatory processes in the placenta and kidney of an sFlt1-based model of early-onset preeclampsia.